Glycemic Index, Glucose Value and Dietary Fiber on Local Foods-Based Analogous Rice Formulations - Suleman, Dininurilmi Putri; Rochmah, Alfi Nur; Zulfa, Fitriyah; Anandito, R. Baskara Katri (South Eastern European Journal of Public Health, 2025)
The food consumed is expected to be useful in maintaining health and preventing disease, even if it is possible that food can cure or eliminate the negative effects of certain diseases. The higher the glucose content in food, the higher the blood glucose levels produced after consumption. Starch-type carbohydrate sources in food can be digested more simply, namely glucose, so that a higher starch content in a food will produce more glucose. One product made from various new carbohydrate sources is analog rice. Analog rice can be used as a food diversification product that can be consumed like eating rice made from rice. Combination cereals and tubers are easy to use to produce food with healthier carbohydrates sources. The purpose of this study is to evaluate the effect of blood glucose and glycemic index after consuming rice analog with various proportions of konjac flour. The result showed that the glycemic index values on analog rice with supplemented konjac flour 2%, 3%%, 4% and 5% were 43.47, 35.26, 25.71, and 19.89, respectively. These values can be categorized as normal GI values, so it can be inferred that the consumption of analogue rice with additional konjac flour does not increase virgin sugar rapidly.